REPRESENTATION OF HUMANITARIAN MESSAGES IN THE COMEDY FILM "AGAK LAEN 2: MENYALA PANTIKU!" (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study examines the representation of humanitarian values ​​in the popular Indonesian comedy film "Agak Laen 2: Menyala Pantiku!" A descriptive qualitative approach was employed to analyze this film—directed by Muhadkly Acho—which garnered an audience of over 11 million. Roland Barthes' semiotic analysis method was used to dissect the visual and textual signs within the film that convey underlying messages regarding humanitarian values. The findings indicate that the film blends elements of dark comedy with the social reality of a nursing home to deliver moral messages concerning humanity, specifically wisdom, steadfastness, compassion, justice, self-control, and quality of character.